Nacre-inspired composite prepared by rolling method I: Effect of particle orientation on deformation behavior. (15th December 2017) - Lee, Yoonjoo; Shin, Dong-Geun; Jeong, Un-Seung; Kim, Soo-Ryong; Kwon, Woo-Teck; Kim, Younghee
Abstract: In this study, we prepared a perfectly ordered nacre-mimetic composite from plate-like alumina particles and epoxy resin using a rolling method. A specific feature of this method is that it progressively aligns the component particles along a single direction regardless of the product thickness at resin contents as low as 25 wt%. The obtained composite exhibited a strength as high as 200 MPa during bending. However, to examine the mechanical properties of artificial nacre, various factors such as the types of initial components and their particle sizes, contents, and orientation degrees must be considered. Hence, this study consists of two parts. The present work (which constitutes the first part) is focused on the orientation effect produced by the plate-like particles and deformation behavior of the composites observed at different orientation degrees. It was found that the obtained composite material with perfectly ordered particles exhibited pull-out behavior similar to that of natural nacre (including the crack propagation route). Further, the fracture toughness of the composite, which was higher than that of alumina, was also affected by its orientation degree.